Fiqih Qada Murafa’at Dalam Hukum Acara Di Peradilan Islam - Salsa Alya Noor Zahra; Masyithah Luthfi; Meki Puspa; Zahratun Nabila; Lisnawati Lisnawati (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2025)
Fikih Qada Murafa’at is a branch of Islamic law that focuses on the judicial process and procedural law in Islamic courts. This study examines the fundamental concepts related to procedural law, including principles of justice, the rights of the parties involved, and fair trial procedures from the perspective of Islamic sharia. This study aims to analyze the application of Fikih Qada Murafa’at in the context of modern Islamic adjudication, with a focus on court procedures, the presentation of evidence, and the rights and obligations of the disputing parties. This study employs a qualitative approach using a case study method through in-depth interviews and analysis of legal documents and court decisions. Furthermore, this article highlights the challenges encountered in harmonizing Islamic legal rules with national legislation. The findings indicate that the principles of Fikih Qada Murafa’at remain relevant in the procedural law process of Islamic courts, although adjustments to the contemporary legal system are necessary. The proper application of these principles can ensure both procedural and substantive justice for all parties involved in legal disputes.